Genotoxicity and mutagenicity induced by acute crack cocaine exposure in mice - Yujra, Veronica Quispe; Moretti, Eduardo Gregolin; Claudio, Samuel Rangel; Silva, Marcelo Jose Dias [UNESP]; Oliveira, Flavia de; Oshima, Celina Tizuko Fujiyama; Ribeiro, Daniel Araki (Taylor & Francis, 2016)
Crack cocaine is an illicit drug derived from cocaine, in which use and abuse have increased around the world, especially in developing countries. Objectives: The aim of this study was to evaluate genomic damage in multiple organs of mice following acute exposure to crack cocaine. For this purpose, single cell gel (comet) assay in peripheral blood, liver, kidney, and brain cells was performed and micronucleus test for bone narrow and liver cells was also made in this setting. Material and methods: A total of 20 C57BL/10 male mice were distributed into four groups, as follows: 0, 4.5, 9, and 18 mg/kg b.w. of crack cocaine dissolved to 1% dimethyl sulfoxide by intraperitoneal (i.p.) route. All animals were sacrificed 24 h after i.p. injection. Results: The results showed that crack cocaine induced DNA damage in peripheral blood, and brain cells for higher doses used as depicted by single cell gel (comet) assay data. Analysis of kidney cells showed no genetic damage for all groups tested. The number of micronucleated cells did not increase after crack cocaine exposure in bone narrow or liver cells. Conclusion: In summary, crack cocaine is a genotoxic agent in peripheral blood, liver, and brain cells but not mutagenic in multiple organs of mice.
Keywords: 50-36-2; crack cocaine; DNA damage; mice